2023
DOI: 10.3389/fonc.2023.1167266
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood derived cellular therapy: advances in clinical development

Abstract: While cord blood (CB) is primarily utilized in allogeneic hematopoietic cell transplantation (HCT), the development of novel cell therapy products from CB is a growing and developing field. Compared to adult blood, CB is characterized by a higher percentage of hematopoietic stem cells (HSCs) and progenitor cells, less mature immune cells that retain a high capacity of proliferation, and stronger immune tolerance that requires less stringent HLA-matching when used in the allogenic setting. Given that CB is an F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 176 publications
0
4
0
1
Order By: Relevance
“…The scientific literature highlights the significant potential of umbilical cord blood (UCB) as a valuable source of stem cells with tolerogenic and immunomodulatory properties [38][39][40]. UCB serves as a source of mesenchymal stem cells [41][42][43] and progenitor hematopoietic cells [44][45][46]. Notably, UCB presents distinct advantages over bone marrow transplants, including lower immunogenicity levels [47][48][49] and reduced requirements for HLA matching [50][51][52], thereby broadening the pool of potential donors and improving accessibility to transplantation and tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature highlights the significant potential of umbilical cord blood (UCB) as a valuable source of stem cells with tolerogenic and immunomodulatory properties [38][39][40]. UCB serves as a source of mesenchymal stem cells [41][42][43] and progenitor hematopoietic cells [44][45][46]. Notably, UCB presents distinct advantages over bone marrow transplants, including lower immunogenicity levels [47][48][49] and reduced requirements for HLA matching [50][51][52], thereby broadening the pool of potential donors and improving accessibility to transplantation and tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The high rejection rate of the donated UCB units due to the strict acceptance criteria for HSCT purposes, in association with the high application of the haploidentical HSCT, have resulted in a significant limitation of the UCB use in the clinic, with a consequent impact on the economic sustainability of the public UCB banks. The perspective of recycling the inappropriate for HSCT units or using the high-quality excess units for isolation and expansion of immune and stem cell populations for cell engineering/reprogramming processes and for production of cell-derivatives for research and clinical applications, extends the therapeutic value of the UCB and increases the sustainability potential of the UCB banks [18,[21][22][23]35,[38][39][40][41][42]52,65,68,70,75,[78][79][80][81][82][83][84][85][86][97][98][99][100]. Novel applications in adoptive immunotherapy, regenerative medicine and specialized transfusion are anticipated not only to maximize the use of the UCB but also to minimize the financial deficit of the public UCB banks through reimbursement procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, PB is not the optimal cell source because it contains few NK cells. In contrast to PB, UCB contains a large amount of NK cells with greater proliferation potential than those from PB, making it a more feasible source for creating CAR-NK cells [ 321 ]. Clinical trials for CAR-NK cells generated from UCB are currently being conducted and showed good safety and efficacy [ 319 , 322 ].…”
Section: Actsmentioning
confidence: 99%